AB0104 ARE POLLUTANTS A NEW RISK FACTOR FOR OSTEOARTHRITIS? RESULTS FROM A SYSTEMATIC LITERATURE REVIEW. (June 2019) - Deprouw, Camille; Courties, Alice; Fini, Jean-Baptiste; Clerget-Froidevaux, Marie-Stéphanie; Demeneix, Barbara; Berenbaum, Francis; Sellam, Jeremie; Louati, Karine
Abstract : Background: Prevalence of knee osteoarthritis (OA) has doubled since the mid-20th century. Interestingly, this increase cannot be explained solely by longer life expectancy and the obesity epidemics (1). Therefore, other environmental factors known to have increased in the recent years could be part of the explanation. Objectives: We performed a systematic literature review (SLR) to summarize the existing knowledge about associations between OA and pollutants. Methods: Pubmed database was used to identify studies reporting data on OA and pollutants in humans (examples of MeSH terms: "Polychlorinated Biphenyls (PCB)" or "Lead"). Abstracts from international congresses were reviewed for the past 2 years, combined with manual curation. Studies were classified in epidemiological clinical studies, pollutants assessments in ex vivo OA joint tissues, and in vitro effect on human chondrocyte. Results: As of January 15, 2019, 193 potentially relevant articles were screened. Among them, 14 were selected. After manual curation, a total of 21 full text articles were analyzed. Ten articles reported epidemiological clinical studies. Four articles underlined the link between PCB and OA: in the 3 articles reporting association with past exposure to PCB, the most robust one showed that risk of OA was significantly increased, at least in men (OR 4.1 [95%CI: 1.8-11.2] for men and 1.3 [95%CI: 0.8-2.3] for women). In the 4 th study, the highest serum concentration of PCB was associated with a higher risk of arthritis: maximal adjusted OR (aOR) was 3.2 [95%CI: 1.6-6.7], p<0.01. However, sensitivity analysis of OA patients did not find any significant association in this study. Two articles focused on serum levels of perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS): aOR to have OA in the PFOA highest serum level quartile was 1.42 [95%CI: 1.26-1.59], p=0.00001 and 1.55 [95%CI: 0.99-2.43]. Data were conflicting for PFOS: aOR to have OA in the PFOS highest serum level quartile was 1.77 [95%CI: 1.05-2.96], p<0.05 and 0.76 [95%CI: 0.68-0.85], p=0.00001. Two articles showed an association between serum lead levels and knee OA in the general population. In Korea, the risk of radiographic OA was increased in the highest quartile of lead serum level compared to the lowest one (aOR 1.90 [95%CI: 1.09-3.32] for men and 1.81 [95%CI: 1.17-2.77] for women). In the United States, risk knee radiographic OA correlates with increased lead serum levels. In the last study, household air pollution induced by the cooking heat source was examined: compared to electricity, the risk of OA was increased with the use of liquids (kerosene/paraffin: aOR 1.73 [95%CI 1.33-2.25]) or solid (coal, wood: aOR 1.73 [1.32-2.27]), (agriculture/crop: aOR 2.0 [1.47-2.72]). Lead and zinc accumulation was reported in 7 articles: 4 of them analyzed the concentration in OA joint obtained during arthroplasty and showed highest concentration in cartilage versus bone. In another, lead serum levels were associated with biomarkers of joint tissue metabolism. Two studies with X-ray fluorescence on cadavers found a high accumulation of lead and zinc in the articular cartilage tidemark. Four studies assessed the in vitro effect of pollutants on human chondrocytes: the viability of chondrocytes was reduced in presence of PCB, gold, silver, fluvic acid and bisphenol A. Conclusion: This SLR suggests a possible link between OA and pollutants but the designs of the studies, the populations investigated and the type of pollutants were still too heterogeneous and limited to conclude definitively that pollutants represent a new environmental risk factor for OA. However, this SLR highlights a critical need for novel epidemiological, clinical and basic research studies in order to identify other potential environmental factors in OA. References: [1] Wallace, PNAS 114(35), 2017 Disclosure of Interests: None declared